The Impact of Young Agricultural Entrepreneurs on Poverty through Gross Regional Domestic Product (GRDP): Towards a Digitalization Strategy - Azzatillah Azzatillah; Tiara Fitri Rizkiyah (Penerbit Goodwood, 2025)
Purpose: This study explores the impact of Young Agricultural Entrepreneurs on poverty reduction through GRDP and proposes a digitalization strategy to enhance their role in promoting economic growth and alleviating poverty in Indramayu. Methodology/approach: Utilizing an explanatory sequential mixed methods design, this research combines secondary data (2020–2024) with quantitative regression analysis (including the Sobel Test for mediation) and qualitative in-depth interviews with 10 Young Agricultural Entrepreneurs in Indramayu Regency. Results/findings: The study finds that Young Agricultural Entrepreneurs significantly reduce poverty but have no significant effect on GRDP, indicating that poverty reduction occurs through direct household mechanisms rather than macroeconomic growth. It suggests that digitalization can enhance their contribution to GRDP by improving productivity, market access, and value-added activities, thereby supporting more sustainable poverty reduction. Conclusion: This study shows that Young Agricultural Entrepreneurs reduce poverty in Indramayu through direct household and local economic impacts. While their activities influence GRDP, the effect is not significant. Digitalization plays a key role in enhancing productivity, market access, and value-added activities, strengthening their contribution to sustainable poverty reduction. Limitations: The study's limitations include its reliance on aggregate secondary data over a relatively short period and a small sample size for the qualitative phase, which may not capture the full diversity of Young Agricultural Entrepreneursexperiences. Contribution: This research offers policy recommendations for empowering Young Agricultural Entrepreneurs through a comprehensive digitalization strategy, thus fostering sustainable economic growth and long-term poverty reduction in rural areas.